Analisis Kurikulum Bahasa Arab Tingkat Mutawassiṭah dalam Pengembangan Maharah Istima’ - Amarulloh; Sulthon, Athian; Ubaid Ridlo; Raswan (Institut Muslim Cendekia, 2026)
This study examines the Arabic language curriculum at the Mutawassiṭah level in relation to the development of listening skills (maharah istimāʿ). As one of the fundamental receptive skills, listening competence serves as the foundation for students’ overall language acquisition. Therefore, analyzing how the curriculum structure, objectives, and instructional content support the development of maharah istimāʿ is essential. This research employs a qualitative approach using document analysis of curriculum documents, syllabi, and Arabic language instructional materials at the Mutawassiṭah level. The data were analyzed through data reduction, data display, and descriptive-analytical conclusion drawing. The findings indicate that the curriculum incorporates objectives and content relevant to the development of listening skills across the affective, cognitive, and psychomotor domains. In the affective domain, the curriculum fosters students’ motivation and positive attitudes toward engaging in listening activities. In the cognitive domain, it emphasizes mastery of phonological features, vocabulary, and grammatical structures that underpin listening comprehension. In the psychomotor domain, structured listening exercises and guided practice are designed to enhance students’ ability to identify sounds, interpret spoken texts, and respond appropriately. Overall, the curriculum demonstrates alignment between learning objectives and instructional content in supporting the systematic development of maharah istimāʿ at the Mutawassiṭah level.